The effects of clinical education program based on Watson's theory of human caring on coping and anxiety levels of nursing students: A randomized control trial. Issue 3 (22nd January 2020) - Durgun Ozan, Yeter; Duman, Mesude; Çiçek, Özlem; Baksi, Altun
Abstract: Purpose: The purpose of this study is to examine the effect of the clinical education program based on Watson's human caring theory on coping and anxiety levels of nursing students. Design and Methods: The research sample consisted of the intervention (n = 53) and the control (n = 53) group. Findings: A statistically significant difference was determined in anxiety mean scores ( P  < .001) and the self‐confident approach, the social‐support seeking approach, the unconfident approach, and the submissive approach subscales of coping with stress in students of the intervention group compared to the control group ( P  < .05). Practice Implications: It is recommended that the clinical education program based on Watson's caring theory is used during the clinical education of nursing students.